Application of restaurant waste lipids (RWL) as a binder component in metal injection moulding - Mohd Amin, Azriszul (2017)
Application of Restaurant Waste Lipids (RWL) is introduced as binder component in metal injection moulding since it’s contains rich amounts of free fatty acids which is suitable as secondary binder components. Different binder formulation of RWL and Polypropylene (PP) were prepared as the binders and the mixture of these binders with water atomized 316L powder were obtained. The suitability application of RWL as binder component was monitored base on mixing condition, rheological characteristic, injection moulding, debinding and sintering process. Mixing time of 90 minutes was obtained as suitable mixing time for producing good homogenise feedstock base on mixing the polypropylene (PP) and RWL. Binder ratio of 50/50 weight percentage between PP and RWL was obtained to be good binder ratio although all binder ratio of 60/40, 40/60 and 30/70 shows pseudoplastic behavior. Taguchi method was successfully employed for optimizing the injection moulding parameters which consists of injection temperature, mould temperature, pressure, packing time, injection time, speed and cooling time. It was found that factors that contribute in injecting good part density and strength were temperature, pressure and speed. Extraction process of RWL using solvent debinding process indicates that hexane solution with temperature of 60ºC and solvent to feeds ratio of 7:1 were better as compare to heptane with respect to fastest time removal. Good thermal debinding process under air atmosphere condition with temperature of 400ºC and heating rate of 30ºC/min was obtained. Sintering of the thermal debound parts also shows good mechanical properties and microstructure of 316L stainless steel parts.